Solution structure and peptide binding studies of the C-terminal Src homology 3-like domain of the diphtheria toxin repressor protein - Wang, Guangshun (The National Academy of Sciences, 1999)
The diphtheria toxin repressor (DtxR) is the best-characterized member of a family of homologous proteins that regulate iron uptake and virulence gene expression in the Gram-positive bacteria. DtxR contains two domains that are separated by a short, unstructured linker. The N-terminal domain is structurally well-defined and is responsible for Fe(2+) binding, dimerization, and DNA binding. The C-terminal domain adopts a fold similar to eukaryotic Src homology 3 domains, but the functional role of the C-terminal domain in repressor activity is unknown. The solution structure of the C-terminal domain, consisting of residues N130-L226 plus a 13-residue N-terminal extension, has been determined by using NMR spectroscopy. Residues before A147 are highly mobile and adopt a random coil conformation, but residues A147-L226 form a single structured domain consisting of five β-strands and three helices arranged into a partially orthogonal, two-sheet β-barrel, similar to the structure observed in the crystalline Co(2+) complex of full-length DtxR. Chemical shift perturbation studies demonstrate that a proline-rich peptide corresponding to residues R125-G139 of intact DtxR binds to the C-terminal domain in a pocket formed by residues in β-strands 2, 3, and 5, and helix 3. Binding of the proline-rich peptide by the C-terminal domain of DtxR presents an example of peptide binding by a prokaryotic Src homology 3-like protein. The results of this study, combined with previous x-ray studies of intact DtxR, provide insights into a possible biological function of the C-terminal domain in regulating repressor activity.